Between Autonomy and Crossing Boundaries: A Sketch on Linguistics as a Scientific Discipline, - Chudzik, Anna (Poznańskie Studia Slawistyczne, 2025)
This article explores the evolution in defining the goals, subject matter and boundaries of linguistics as an academic discipline. The discussion has two goals: to demonstrate shifts in the understanding of the essence of linguistics and to provide a synthesized overview of changes in methodological tools and the scope of linguistic research, particularly those arising from interdisciplinary collaboration. The article outlines the historical context for the formation of linguistics and its research focus, and it synthesizes potential mechanisms for expanding the boundaries of linguistic inquiry (redefining research objectives, paradigm shifts, and interdisciplinary approaches) as well as forms of openness to collaboration (interdisciplinarity, complementarity, and transdisciplinarity). The conclusions consider the implications of these shifts in the self-definition of linguistics for research outcomes.